1988
DOI: 10.5144/0256-4947.1988.194
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Practices in Riyadh, Saudi Arabia

Abstract: Infant-feeding patterns were studied in 6,623 randomly selected Saudi families living in Riyadh. The 4,796 infants studied were under 1 year of age and were fed with breast milk plus bottle complements. Bottle-feeding was started in 27.3% of infants during the first month after birth. The mean age at which solid food was introduced was 3.45 months. The overall results suggest a decreasing incidence of breast-feeding along with diminishing length of nursing period.AR Al-Frayh, SS. Wong, KN. Hague, Infant Feedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…In 1988, Al-Frayh et al reported on infant feeding practices in 4796 infants under 1 year of age living in Riyadh and found that the average duration of breastfeeding was 5.05 months, while bottle feeding was started under 1.0 month of age in 27.3% and the mean age for starting solid food was 3.5 months 11. In another nutritional survey conducted in several semirural areas of Saudi Arabia, Al-Othaimeen et al found that 21.5% of 767 children were breastfed completely, 68.4% used mixed feedings and about 10% did not breastfeed 12.…”
Section: Discussionmentioning
confidence: 99%
“…In 1988, Al-Frayh et al reported on infant feeding practices in 4796 infants under 1 year of age living in Riyadh and found that the average duration of breastfeeding was 5.05 months, while bottle feeding was started under 1.0 month of age in 27.3% and the mean age for starting solid food was 3.5 months 11. In another nutritional survey conducted in several semirural areas of Saudi Arabia, Al-Othaimeen et al found that 21.5% of 767 children were breastfed completely, 68.4% used mixed feedings and about 10% did not breastfeed 12.…”
Section: Discussionmentioning
confidence: 99%
“…18 In a study from Riyadh, 31.3% of children were breastfed alone, 59.4% were fed with breast and bottle and 9.3% were fed by bottle alone. 19 Another study of 250 children from Riyadh at one month of age revealed that 42% were on mixed feeding, 31% were bottle fed and remaining 27% were totally breastfed. 20 In a nationwide survey mentioned earlier, 16 the duration of breastfeeding for the last born child was 12.5 months.…”
Section: Discussionmentioning
confidence: 99%
“…In an earlier study from Riyadh, the mean duration of breastfeeding for children between 6 and 8.9 months was 4.66 months and between 9 and 12 months of age was 5.99 months. 19 …”
Section: Discussionmentioning
confidence: 99%
“…Some of these beliefs can be harmful and could be related to the decline in breastfeeding, which has been documented in the Saudi Arabia. 38 , 39 …”
Section: Introductionmentioning
confidence: 99%